ISLAM DI TANAH BANJAR - Abdul Wahab Syakhrani; Ahmad Rangga Islami (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
The entry of Islam to South Kalimantan was not identical with the establishment of the Banjar Kingdom (Banjarmasin). Furthermore, the renewals and dissemination of Islamic teachings directly sourced from Mecca only started at the beginning of the 18th century, namely by Sheikh Muhammad Arsyad al Banjari. In an effort to spread Islamic teachings, he conducted recitations and spread his children and grandchildren/students to remote areas of South Kalimantan, as well as writing religious books which were then spread in several regions in the archipelago and even reached and used in several Southeast Asian countries.